Communities in economic crisis : Appalachia and the South - Gaventa, John, 1949-; Smith, Barbara Ellen, 1951-; Willingham, Alex W., 1940- (Labor and social change., 1990)
Resisting injustice in Appalachia and empowering residents to build democratic alternatives to the heritage of enduring poverty.